Reflecting on the importance of open communication and social capital for the co-creation of knowledge in Irish fisheries - Calderwood, Julia; Pedreschi, Debbi; Ó Cuaig, Macdara; Reid, David G. (Frontiers in Marine Science, 2023)
Fishing industry stakeholders have unique and important contributions to make to fisheries research. Co-operative and collaborative research approaches between science and industry are important to facilitate the documentation of fishers’ knowledge and the co-creation of common understandings. Successful collaborations require open communication, trust and social capital, but numerous barriers exist to establishing these effective partnerships. This paper takes a narrative approach to reflect on the authors’ experiences of engaging and collaborating with Irish fishers in the quest for the co-creation of knowledge, while considering how data from industry can best be used and integrated into scientific processes. This includes reflecting on barriers faced, in addition to motives and opportunities that have enabled this work to progress. Through case study examples, we reflect on issues surrounding misunderstandings regarding the roles of scientists and the scientific process, a lack of transparency, a lack of trust, historical/legacy issues, and contemporary pressures including the COVID-19 pandemic and impacts of Brexit. Building trust and active communication are identified as key elements to effectively co-create knowledge and common understanding. Trust is often developed in an informal setting, but more formalized processes, increased transparency and opportunities to engage, and institutional supports may further facilitate effective knowledge co-creation in fisheries.